Teaching with comics and graphic novels fun and engaging strategies to improve close reading and critical thinking in every classroom - Smyth, Tim (Routledge eye on education, 2022)
"This text will allow you to harness students' love of comics and graphic novels while increasing critical thinking and engagement in the classroom. Author Tim Smyth offers a wide variety of lessons and ideas for using comics to teach close reading, working with textual evidence, literature adaptations, symbolism and culture, sequencing, essay writing, and more. He also models how to use comics to tackle tough topics and enhance social emotional learning. Throughout the book, you'll find a multitude of practical resources including a variety of lesson plans-some quick and easy activities as well as more detailed ready-to-use unit plans. These thoughtful lessons meet the Common Core State Standards and are easy to adapt for any subject area or grade level to fit into your curriculum. Add this book to your professional library and you'll have a new and exciting way of reaching and teaching your students!"--